Pengaruh Optimalisasi Biaya Operasional Sebagai Strategi Keuangan Dalam Meningkatkan Profitabilitas Di PT MSAL - Ayu Diah Dwi Astuti (Lembaga Pengembangan Kinerja Dosen, 2024)
Good financial management has a central role in business, involving managing funds effectively and efficiently to maximize profits and company value by managing financial risks. Profitability ratios, especially Return on Equity (ROA), are the main indicators in measuring a company's ability to generate profits. Optimizing operational costs is a key strategy in increasing profitability. This research focuses on PT MSAL, an oil palm plantation company that is trying to increase profitability through optimizing operational costs. A quantitative approach with simple linear regression analysis was used as the research method. Secondary data in the form of financial reports for the last three years (2020-2022) as research objects. The results of the analysis between operational costs and company profitability prove that there is a positive and significant influence. The partial hypothesis test shows that operational costs have a statistically significant impact on profitability. Simple linear regression analysis produces a regression line equation, and the coefficient of determination shows that operational costs have a contribution of 99.4% to the company's profitability. Operational costs have an important role in determining PT MSAL's level of profitability. Optimizing operational costs can improve a company's financial performance. Therefore, companies are advised to continue to evaluate, develop efficient business strategies, and regularly monitor the relationship between operational costs and profitability.